A study on attitude of contraceptive method users towards newer contraceptive method (ormeloxifene) - Sehgal, Vinika; Agarwal, Shaily; Gupta, Renu; Dwivedi, Seema; Verma, Pratima (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: This study aimed to asses user attitudes towards newer contraceptive method-Chhaya (ormeloxifene). It assessed the frequency of use, side effects, discontinuation rates, fertility return, and user satisfaction, providing insights into how this method is perceived and experienced. Methods: The study was conducted from June 2022 to June 2024 at GSVM Medical College, Kanpur, and included 200 women of reproductive age. Participants were recruited from the outpatient department and postpartum wards, with data collected on demographics, reproductive health, contraceptive side effects, and satisfaction using a standardized questionnaire. Statistical analyses, including chi-square and Pearson’s correlation tests, were applied using Origin Pro software. Results: Chhaya users accounted for 9.558% of total OPD attendance. Fertility return was quicker with 46.66% regaining fertility within 6 months of discontinuation. Major side effects -among study participants were delayed cycles (26.92%) and breast tenderness (23.07%). Discontinuation rates were found to be 19.71% discontinuing after 3 months. Satisfaction levels with 32.5% very satisfied were found in the study participants. Conclusions: Chhaya was associated with a quicker return to fertility, fewer severe side effects, and higher user satisfaction.